2022
DOI: 10.1177/09504222221100343
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for problem-based learning in higher education: Lessons from a cross-program Industry 4.0 case

Abstract: This article aims to identify the challenges and opportunities in cross-program problem-based learning (PBL) in higher education, based on an Industry 4.0 case with undergraduate and graduate students studying for engineering degrees. The method for this research comprised a cross-program course structured to bring together undergraduate and graduate students using a PBL approach. Five Industry 4.0-related projects were developed in collaboration with four multinational companies. The authors present the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Motivasi belajar memiliki poros penting dalam proses pembelajaran (Ansari, 2024;Ates, 2024;de Andrade Gomes, 2024;Arici, 2023;Yeung, 2023). Melalui motivasi yang tinggi membantu siswa untuk meraih prestasi yang optimal dalam belajar (Amin, 2023;Arruzza, 2023;Ayerbe-López, 2023;Connolly, 2023;Salvador, 2023). Sedangkan motivasi belajar yang rendah dapat menghambat siswa dalam mencapai hasil belajar yang memuaskan (Das, 2023;Peng, 2023;Puranik, 2023;Sharma, 2023;Uluçinar, 2023).…”
Section: Pendahuluanunclassified
“…Motivasi belajar memiliki poros penting dalam proses pembelajaran (Ansari, 2024;Ates, 2024;de Andrade Gomes, 2024;Arici, 2023;Yeung, 2023). Melalui motivasi yang tinggi membantu siswa untuk meraih prestasi yang optimal dalam belajar (Amin, 2023;Arruzza, 2023;Ayerbe-López, 2023;Connolly, 2023;Salvador, 2023). Sedangkan motivasi belajar yang rendah dapat menghambat siswa dalam mencapai hasil belajar yang memuaskan (Das, 2023;Peng, 2023;Puranik, 2023;Sharma, 2023;Uluçinar, 2023).…”
Section: Pendahuluanunclassified
“…Meanwhile, for mothers, omega-3 is also needed to maintain the mother's immune system. Fish is also a source of animal protein which is needed to support the health of the mother and fetus (Salvador et al, 2023). Beef contains iron, protein and zinc.…”
Section: Percentage Of Increase In Student Scores On the Application ...mentioning
confidence: 99%
“…The opportunity would then exist for students to compare their performance and employability markers against benchmark data from their peers or previous cohorts. Comparing manager scores with self-perceived scores of employability markers can also be beneficial since 360-degree feedback has been shown to enhance student learning (Salvador, 2022). The impact may also be significant since an empirical study involving circa 3000 managers and 200 organisations found that students completing a placement reported lower self-perceived employability levels than their manager’s assessment (Hughes, 2022).…”
Section: Opportunities For Studentsmentioning
confidence: 99%